Productivity, water use efficiency and soil properties of sugarcane as influenced by trash mulching and irrigation regimes under different planting systems in sandy loam soils - Kumar, Navnit; Sow, Sumit; Rana, Lalita; Kumar, Vipin; Kumar, Jyotish; Pramanick, Biswajit; Singh, A. K.; Alkeridis, Lamya Ahmed; Sayed, Samy; Gaber, Ahmed; Hossain, Akbar (Frontiers in Sustainable Food Systems, 2024)
Introduction In the era of climate change, sugarcane used to face a problem associated with water shortage due to erratic rainfall patterns and lowered water tables. Improved water use efficiency using innovative crop management strategy is needed for sustainable sugarcane production. Trash mulching with different irrigation regimes can effectively modify the plant's hydrothermal micro-environment for increasing cane yield and water productivity. Methods Keeping this in the background, a field experiment was conducted at Sugarcane Research Institute, RPCAU, Pusa, India, from 2016–17 to 2018–19 to investigate the effects of trash mulching and irrigation regimes on sugarcane productivity, water use efficiency (WUE) and soil properties in different planting systems. The field experiment comprised 12 treatments including four planting methods viz. conventional flat planting (CF; 75 cm row spacing) with trash mulching (6 t ha−1), CF planting (75 cm row spacing) without trash mulching (6 t ha−1), paired row trench (PT) planting (30: 120 cm row spacing) with trash mulching (6 t ha−1), PT planting (30: 120 cm row spacing) without trash mulching (6 t ha−1) and three irrigation schedules consisted of irrigation water (IW); cumulative pan evaporation (CPE) ratio of 0.60, 0.80, and 1.00 was laid out in strip plot design with three replications. Results and discussion The cane yield (103.5 t ha−1) was found significantly higher in PT planting with trash mulching over the CF planting method with or without mulching. Concerning irrigation regimes using the IW/CPE ratio, it was found that the IW/CPE of 0.6 resulted in 16.9, 13.3% higher water-use efficiency, and 37.1, 40.7% higher water productivity over those under IW/CPE of 0.8, and 1.00, respectively. Furthermore, soil parameters like soil microbial biomass carbon (SMBC) and dehydrogenase activity were increased by 12.5, and 17.5 % due to trash mulching with trench planting as compared to those under conventional flat planting without mulching. The results suggest that planting sugarcane in paired rows and irrigation scheduling at 1.00 IW/CPE with the adoption of trash mulching practices is effective for increasing profitability by way of higher sugarcane productivity and water productivity and also in sustaining soil health.